Facile method to fabricate carbon fibers from textile-grade polyacrylonitrile fibers based on electron-beam irradiation and its effect on the subsequent thermal stabilization process - Yoo, Seung Hwa; Park, Sejoon; Park, Youngkyu; Lee, Donggyun; Joh, Han-Ik; Shin, Ickgy; Lee, Sungho (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
An electron-beam was irradiated on textile-grade polyacrylonitrile (PAN) fibers at various electron doses (200, 500, 1000, and 1500 kGy) prior to the thermal stabilization to fabricate carbon fibers (CFs). Textile-grade PAN fibers experienced superficial fusion between filaments during the thermal stabilization due to a large amount of co-monomer contents. However, electron-beam irradiation prior to thermal stabilization prevented the superficial fusion. Furthermore, the total stabilization time required to achieve the same degree of stabilization was effectively reduced as 64% by electron-beam irradiation. Various radicals were formed within textile-grade PAN fibers and they were recombined to crosslink with each other by gradually increasing the temperature. As a result, the elongation of irradiated fibers was suppressed and the glass transition temperature shifted to higher temperatures compared with the pristine fiber by increasing the electron dose. On the other hand, the onset and peak temperature of cyclization reaction for irradiated fibers were shifted to lower temperatures which indicated that the cyclization reaction was initiated at lower temperatures than pristine fibers. The tensile strength, Young's modulus, and strain-to-failure of resulting CFs were 1.83 +/- 0.23 GPa, 147.44 +/- 4.55 GPa, and 1.30 +/- 0.15%, respectively. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: PAN FIBERS; PRECURSORS; COPOLYMERIZATION; CARBONIZATION; PERFORMANCE; RADIATION; EFFICIENT; POLYMERS; CHLORIDE